A Framework for Assessing the Quality of Democratic Deliberation: Enhancing Deliberation as a Tool For Bioethics - De Vries, Raymond (2011)
The goal of democratic deliberation (DD) bioethics research is to elicit informed and considered opinions on ethically controversial issues. But the trustworthiness of DD outcomes depends on the quality of deliberations. We provide a framework to evaluate the quality of deliberations and apply that framework to a DD project on surrogate consent for dementia research involving randomly selected samples of the older general public. Using a mixed method approach, we found that participants were very satisfied with the sessions, learned and used new information, were respectful and collaborative, and were able to “reason together” to arrive at societal policy recommendations. Implications and limitations of the paper are also discussed.